Modified procedure for the simultaneous determination of nitrogen, phosphorus and sulphur by hydrogen peroxide microwave digestion and ion chromatography - Colina, Marinela; Gardiner, P. H.; Rivas, Zulay; Troncone, Federico (Ciencia)
A modified method for the microwave oxidation with hydrogen peroxide of nitrogen, phosphorus and sulphur followed by the determination of the nitrate, phosphate and sulphate ion by ion chromatography is presented is this work. This method was modified in order to applied the methodology in more recalcitrant compounds where nitrogen, phosphorus and sulphur atoms were in ring system. The developed procedures were validated using pure compounds: sodium nitrite, sodium sulphite, L-cysteine, lysine, phosphonitrile chloride, saccharin, urea, and reference material prawn GBWO8572. Three steps procedure was necessary to digest compounds with a ring in the structure. The amount of recovery after each step in the modified method could be indicative of the nature of the compounds present in the sample. The maximumlevels of phosphorus encountered in Lake Maracaibo (ca. 20.3 mg/L) correspond to a general level of productivity of a hyper-eutrophic lake.